BRIDGING GAPS IN ENGLISH FOR SPECIFIC PURPOSES (ESP) EDUCATION: RECOMMENDATIONS FOR PRACTICAL PEDAGOGICAL INNOVATION - Pratiwi, Widya Rizky (Publikasi dan UKI Press UKI Toraja., 2024)
English's position as the global lingua franca facilitates communication across myriad industries, none more so than publishing. By a comprehensive literature review synthesising insight from previous research, this current study identifies challenges in ESP in publishing amid its significance and innovative pedagogical approaches. Limited exploration of emerging trends, underrepresentation of diverse publishing contexts, limited focus on interdisciplinary perspectives, etc., were found as gaps. Some innovative pedagogical approaches for publishing professionals and scholars and recommendations were revealed to address existing gaps and contribute to advancing knowledge in English for Specific Purposes in publishing. By addressing these gaps, scholars can contribute to a more nuanced understanding of ESP in publishing and inform the design of targeted language learning interventions to meet the evolving needs of publishing professionals in diverse contexts